Effect of plant densities and cultivars on vegetative and productive variables of European pears in southern Brazil - Machado B.D.* (2014)
The pear is the third most produced deciduous fruit in the world and the third most consumed in Brazil. However, a lack of technological information about the behavior of European pears cultivars and definition of the most appropriate plant density has limited the culture development. This study aimed to evaluate the effect of two plant densities and three European pear cultivars grafted on Adams quince rootstock for vegetative and productive variables like growth, development and fruit production. The experiments were conducted in a commercial orchard in edaphoclimatic conditions of upland region of southern Brazil, located at 1,425 m AMSL, during three growth seasons: 2008/09, 2009/10 and 2010/11. The cultivars evaluated were 'Santa Maria', 'Rocha' and 'Abbé Fétel' grafted on Adams quince rootstock and the plants densities were 7,500 and 2,500 trees ha-1 with a spacing of 1.0 and 0.3 m between trees and 4 m between rows, respectively and the conduction system of central leader The following variables were evaluated: plants height increment (PHI), canopy volume increment (CVI), cultivars trunk diameter increment (CTDI), rootstock trunk diameter increment (RTDI), estimated yield (EP) and productive efficiency (PE). The 'Abbé Fétel' cultivar at 2,500 trees ha-1 density showed a bigger and significant CVI, CTDI and RTDI, which corresponded to a high vigor trees and leading consequently to a lower yield (294.60 t ha-1) and productive efficiency (0.023 kg cm-2) when compared with the others cultivars. Santa Maria cultivar at the same plant density with intermediate vigor plants, showed a lower CVI, CTDI and RTDI and consequently high yield (4,601.3 t ha-1) and productive efficiency (0.84 kg m-3). The plant densities did not influence Abbé Fétel yield. However, the yield of Santa Maria and Rocha cultivars increased 77% and 24% respectively at 7,500 trees ha-1 when compared to 2,500 trees ha-1 at the edaphoclimatic conditions of upland regions of Southern Brazil.